FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - Shelly Elinda Maulidina, 14.05.52.0152; Nurhayati, Ida (Students Journal of Accounting and Banking, 2018)
This study examines the effect of profitability, debt to equity ratio, firm size, firm age, and auditorâs opinion on manufacturing company listed in Indonesia Stock Exchange. This study used purposive sampling method in sample selection, the criteria for a sample is manufacturing company listed in Indonesia Stock exchange during the period from 2013 to 2016. Based on the criteria, obtained a sample of 320 companies over a four-year observation period. Relationship and (or) influence between variable is described by using logistic regression analysis. The result showed that debt to equity ratio variable has negative effect significant to the timeliness of financial report, firm age variable and auditorâs opinion had positive effect significant to the timeliness of financial report. Profitability variable has positive effect not significant to the timeliness of financial report, firm size variable has negative not significant to the timeliness of financial report.Keyword: timeliness, profitability, debt to equality ratio, firm size, firm age, and auditorâs opinion